Evaluation of controls, quality control assays, and protocol optimisations for PacBio HiFi sequencing on diverse and challenging samples - Bronner, Iraad F.; Dawson, Emma; Park, Naomi; Piepenburg, Olaf; Quail, Michael A. (Frontiers in Genetics, 2025)
The Darwin Tree of Life (DToL) project aims to generate high-quality reference genomes for all eukaryotic organisms in Britain and Ireland. At the time of writing, PacBio HiFi reads are generated for all samples using the Sequel IIe systems by the Wellcome Sanger Institute’s Scientific Operations teams, however we expect lessons from this work to apply directly to the Revio system too, as core principles of SMRT sequencing remain the same. We observed that HiFi yield is highly variable for DToL samples. We have investigated what drives this variation, and potential mitigations. To support these investigations a number of controls were evaluated to ensure that the library and sequencing preparation procedures, reagents, consumables, and Sequel IIe instruments, were performing as expected. Our findings support that a primary factor driving variability in HiFi yield is the quality of the DNA prior to library construction, e.g., purity, size, and damage. We investigated whether quality assessment assays could link measurable DNA damage or purity to sequencing yield. Some correlation could be established, however no assay was predictive of sequencing yield for all samples, indicating that the variability is driven by multiple factors that may interact. We demonstrate that contaminants present in some samples are the cause of very low HiFi yield, and show that these contaminants can negatively affect the PacBio internal sequencing control and samples multiplexed on the same SMRT Cell. We found that consistently high yields could be obtained if an amplification workflow was utilised, namely PacBio’s ultra-low input library preparation protocol.